Pengaruh Kesadaran Linguistik dan Kesadaran Persepsi Visual Terhadap Kemampuan Membaca Permulaan Anak Tunagrahita - Endang Rochyadi (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
this study was conducted to find the essential factors of linguistic awareness and visual perception influencing the beginning reading skill of mentally retarded children. The factors studied include linguistic awareness (morphemes, semantics and syntax) and visual perception awareness (visual discrimination, visual spatial, visual figure-ground, and visual memory) which are assumed to be the prerequisites of learning early reading. The subjects of this research were 32 students from 5 special school in Bandung. The results show that both of the factors have strong influence towards mentally retarded children early reading skill. However, the Beta Coefficient it was is found that linguistic awareness has stronger relationship compared to the visual perception aspect. The value of the coefficient path in the linguistic awareness is 0.72, while the coefficient path value for linguistic awareness is 0.25. This means that linguistic awareness is influencing position as the prerequisite of early reading skill compared to the visual perception aspect. However, if studied further, it is found that not all variables related to either linguistic awareness aspect or visual perception have the same meaningful relationship with children reading skills. The most essential factor of reading prerequisite related to the linguistic awareness is related to the phoneme and syntax awareness, while the essential factor in visual perception is related to the visual discrimination and visual memory.Â ABSTRAKKajian ini untuk melihat faktor-faktor esensial dari kesadaran linguistik dan kesadaran persepsi visual yang mempengaruhi kemampuan membaca permulaan pada anak tunagrahita. Faktor-kator yang dikaji meliputi kesadaran linguistik (fonem, morfem, semantik dan sintaksis) dan kesadaran persepsi visual (visual discrimination, visual spacial, visual figure and ground, visual memory) yang diduga menjadi prasyarat dalam belajar membaca permulaan. Subjek penelitian berjumlah 32 siswa dari lima SLB di Bandung. Hasil kajian ini menunjukkan, bahwa kedua faktor tersebut memiliki hubungan kuat terhadap kemampuan membaca permulaan anak tunagrahita. Berdasarkan Koefisien Beta secara parsial kesadaran linguistik memiliki hubungan jauh lebih kuat dibandingkan kesadaran persepsi visual. Nilai koefisien path kesadaran linguistik (0.72) sementara pada kesadaran persepsi visual nilai koefisien pathnya (0.25). Akan tetapi ada faktor esensial sebagai prasyarat membaca yang berkaiatan dengan aspek kesadaran linguistik yaitu kesadaran fonem dan sintaksis, sementara faktor esensial pada aspek kesadaran persepsi visual lebih berhubungan dengan discrimination dan visual memory.Â